2022
DOI: 10.1097/md.0000000000030425
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of pre-procedural anxiety for repeat sessions in extracorporeal shockwave lithotripsy (ESWL) reduces pain intensity: A prospective observational study

Abstract: Pain control is a major determinant for successful stone clearance in extracorporeal shockwave lithotripsy (ESWL) for urolithiasis. Pain perception during ESWL may be influenced by patient factors like gender, age, body habitus and anxiety level, and stone related factors like size, laterality and location of stone. We investigated in general, the confounding patient and stone factors influencing pain perception during ESWL with importance given to procedural anxiety in first and the subsequent session of ESWL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Experimental and clinical studies have well supported the effects of acupressure on pain relief, stabilization of physiological indicators, and reduction in analgesic consumption [ 13 , 17 ]. Also, it has been reported that there is a direct correlation between pain and patient satisfaction [ 18 ], and patients undergoing ESWL may need repeated treatment sessions [ 19 ]. This non-pharmacological method is effective, safe, and cost-effective, providing pain relief with patient satisfaction without additional equipment [ 12 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental and clinical studies have well supported the effects of acupressure on pain relief, stabilization of physiological indicators, and reduction in analgesic consumption [ 13 , 17 ]. Also, it has been reported that there is a direct correlation between pain and patient satisfaction [ 18 ], and patients undergoing ESWL may need repeated treatment sessions [ 19 ]. This non-pharmacological method is effective, safe, and cost-effective, providing pain relief with patient satisfaction without additional equipment [ 12 , 20 ].…”
Section: Introductionmentioning
confidence: 99%